Update records and distribution of Digitonthophagus gazella (Coleoptera: Scarabaeidae) in Argentina: A potential invasive species - Guerra Alonso, Celeste Beatriz (2022)
The distribution of Digitonthophagus gazella in Argentina is updated. A total of 246 individuals were captured between 2012 and 2022, through different techniques, including manual collection, light traps, and baited pitfall traps. The species is present in ten provinces, six of which are first records. In addition, D. gazella was recorded for the first time in five ecoregions, Atlantic Forest, the Espinal, Subtropical Grasslands, Northern Monte, and Parana Delta. The potential consequences of this introduced species on native dung beetles assemblages should be assessed in future studies.